Creative Writing Starts with a Sentence: Keep the Human in Humanities - Klos, Kathleen (University of Wisconsin-Stevens Point, 2018)
The following research discusses creative writing and structures itself around big ideas—be those past, present, or future. Current scholars, students in elementary, middle, high, and post-secondary institutions, as well as the every day writer poring over drafts at Starbucks, may be noticing a shift in attitude toward creative writing and humanities classes. Reformation winds are pushing the sails of creative writing in different directions. Some individuals remain magnanimous about the field of liberal arts, while others are willing its extinction in education altogether. Educational practices of 2018 are so far removed from the traditional way things used to be in the early 2000s, where consequential curriculum, retention in school from poor grades and behavior, and parents who parented were evident. Education and respect for such a valuable profession is the worst it has ever been because teachers don’t feel valued. More so, students do not know how to write a sentence, let alone craft something creative. From origin to present day, creative writing under the umbrella of liberal arts education is a topic worthy of its surge in current research. This research focuses on the benefits of teaching creative writing, highlights viewpoints of individuals who scoff at its presence—especially in present day data-driven school curriculums—and discusses this type of writing as engaging student imagination, promotive of problem-solving skills, and fosters critical thinking. A fortiori, it is a societal duty to make sure creative writing stays in school curriculums for the well-being of the writer in all of us. The future of creative writing hangs in the balance of administrative hands—whose ruthless attitudes can either make or break a child’s pursuit of understanding, dignity, self-awareness and happiness.